2015
DOI: 10.1080/14733315.2015.11684086
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Characteristics and Frequency Spectrum Analysis of Fan Induced Airflow Compared with Natural Winds

Abstract: Electric fans used for cooling or local ventilation are common household appliances around the world, especially in developing countries. They offer many advantages such as low cost and energy savings, as well as easy implementation. However, the airflow from fans is often considered to be less comfortable than the sensations produced by natural winds. In order to avoid the draught induced by fans, and to investigate dynamic airflow characteristics of household fans, an anemometer was utilized to measure the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The β values for the forest park and the naturally ventilated room, i.e., 1.22 and 1.70, were much higher than that for the mechanical wind which is 0.48. This is consistent with the results by Gao et al [43] and Ouyang et al [44].…”
Section: Air Parameterssupporting
confidence: 94%
“…The β values for the forest park and the naturally ventilated room, i.e., 1.22 and 1.70, were much higher than that for the mechanical wind which is 0.48. This is consistent with the results by Gao et al [43] and Ouyang et al [44].…”
Section: Air Parameterssupporting
confidence: 94%
“…Figure 12 shows the velocity distribution and power spectral density functions for different conditions. 25,26 Ouyang et al 27 reported that the critical b value to distinguish mechanical wind from natural wind is 1.0-1.1 in human perceptual velocity range. Figure 13 presents power spectrum curves at different positions.…”
Section: Spectral Analysis Of Air Velocity Signalmentioning
confidence: 99%